Effect of Thymoquinone on skeletal muscle regeneration via assessment of Pax-7 and Myo-D expression in the DMBA-treated hamster pouch - Swidan, Sara Ali; El Azab, Samia A.; Hassan, Magda Mohamed Aly (Brazilian Dental Science, 2023)
Objective: Pax-7 and Myo-D regulate satellite cells’ activation and differentiation, thus muscle regeneration following damage. This research aimed to investigate the effect of Thymoquinone (TQ) on skeletal muscle regeneration following 7,12-dimethylbenz-(a)-anthracene (DMBA)-induced injury in the hamster buccal pouch via immunohistochemical assessment of Pax-7 and Myo-D expression. Material and Methods: 65 male golden Syrian hamsters were divided into 3 groups: Group 1: (n=5) received no treatment. Group 2: (n=20) served as a positive control. The left buccal pouches were painted with the carcinogen 3/week/ 6weeks. Group 3: (n=40) were subdivided into two equal sub-groups as follows: Group 3a: (n=20) were given one i.p. TQ injection. Group 3b: (n=20) were given two i.p. TQ injections. Five animals from each group (2 and 3) were euthanized at 24, 48 hrs, one, and two weeks after the last injection. A blood sample (2 ml) was withdrawn for assessment of TNF-alpha levels in serum. Serial sections of the pouches were examined histologically (H&E), and immunohistochemically (IHC) for the detection of Pax-7 and Myo-D proteins. Results: double i.p injections of TQ resulted in a significant elevation in the level of TNF-alpha from the second-day post-injection with a progressive formation of the muscle fibers (MFs) and mononuclear cells (MNCs) around the deeper blood vessels. At 14 days, no statistically significant difference was found between this group and group ‘2’, while the difference remained significant compared to groups ‘1’ and ‘3a’. The muscle fibers were more mature and compact. IHC results showed positive expression of the perivascular mononuclear cells (MNCs) to both Pax-7 and Myo-D with positive reactivity of the peripheral nuclei of muscle fibers to Pax-7 compared to the negative reaction in the positive control group. Conclusion: early and two TQ injections had a promising effect on the induction of striated muscle regeneration, mainly by non-myogenic stem cells.KEYWORDSThymoquinone; Pax-7; Myo-D; Buccal pouch; Muscle regeneration.